Strengthening the Community Economy Through Halal Law - Mashudi, Mashudi; Barowi, Barowi (PT Aksara Indo Rajawali, 2025)
A people's economy is interpreted as a democratic economy aimed at the prosperity of the people without exception. The economic system implemented by a country depends on the strength and economic conditions in that country. The halal legal culture approach is currently seen as effective and efficient in resolving people's economic problems. That is why this strategy is being developed in many countries, including Indonesia. Legal culture means the overall attitude of society and a system of values that can determine how the law should apply and provide a proper place for humans with the presence of the law. With in-depth analysis, this work finds two ideals: First, halal or similar terminology is a need for all religious communities so there should be no discrimination; Second, implementing a halal legal culture is a very appropriate strategy to strengthen the sustainability of the people's economy. Halal businesses are essentially the saviors of humanity, where meaningful aspirations and endeavors can promise true salvation. It is worth mentioning that the halal business will deliver tayyib, which means that the basic requirements for producing items are based on the principles of halal and also set higher quality standards.